The Effect of Parenting Styles, Personalities, Bully Behaviors Towards Suicide Attempt - Azizi Yahaya; Balan Rathakrishnan; Halimah Maalip; Peter Voo Su Kiong; Dahlan A. Malek; Muhammad Idris Bullare @ Bahari (Southeast Asia Psychology Journal, 2023)
The aim of this study is to identify the association between parenting styles, personality, bullying behavior, and suicide attempt among adolescents in Kota Kinabalu, Sabah. This study is a descriptive-correlation quantitative study that emphasizes the relevance of variable variation and its relationship with other variables. Statistical analysis showed good reliability and validity of the research instruments. The reliability of the Parental Authority Questionnaire (PAQ) is .786; Big Five Inventory (BFI) is .702; the Measure of Bullying Behaviour-Adaptation (MBBS-A) is .824; and The Suicide Probability Scale (SPS) is .924. While the validity of all research instruments is good as the obtained value (p table) is greater than the critical value (r table) of .2542 and significantly high because  < .05. The samples of the study were selected using the cluster sampling method and consisted of secondary school students in Johor. A total of 815 data were used for descriptive analysis while 659 data that had gone through the process of screening and normality analysis were used for inferential analysis. The findings showed that the level of suicide attempts among adolescents is high (45.6%). In addition, this study showed that the authoritative parenting style is the most dominant with a mean of 3.53; verbal bullying is the most dominant bullying behavior with a mean of 1.76; and agreeableness is the most dominant personality domain with a mean of 3.59. The results of the Stepwise-Multiple Regression analysis showed that social manipulation, verbal and, physical bullying behavior, agreeableness and conscientiousness in personality, and authoritative parenting styles are predictors of suicide attempts.